Poetic devices in the construction of Behnam Atallah's selected poems - Alhadithy, Samer Ibrahim Jubair (2018)
Bahnam Atallah's poetry has drawn the attention of researchers, who have conducted studies on his collections issued. However, they have not addressed all that is worth investigating. Moreover, their approaches were devoid of clarity of vision as well as delving far away from his lexical linguistic. Therefore, this research is destined to focus on how the poet employs artistic elements in constructing the selected poetic texts in order to achieve the two objectives of the study: highlighting the elements of the artistic structure in Bahnam’s poems, and analysing the elements of the artistic structure in his poems. The researcher selected five poetry collections published during the period between 1982 and 2012. The researcher adopted the analytical descriptive methodology that was employed by Dr. (Youssef Bakkar) in which he focused on the ternary artistic construction elements namely (poetic language, poetic image, poetic rhythm) which is suitable for this type of study, due to its artistical and aesthetic nature in helping to analyse and interpret the selected texts in general. It is an analytical descriptive approach based on tracing the origins of the poetic texts, exploring their meanings and demonstrating their most prominent themes. The researcher came to the conclusion that the construction of the language of the selected texts, as they appear in the poetic lexicon, is to use a distinctive Lexis, and the combination of the natural lexicon, the legendary, the geographical and the dictionary of other languages. As well as the linguistic stylistic phenomena, which is one of the most important linguistic methods of stylistics, is repetition and questioning with a coaxing style. While his poetic images, with its different branches of formulation, composition, deconstruction and imagery, are addressed by the poet in his poems, he used his imagination to create intelligent images out of the ordinary, tangled with each other and composed like a painting. The poetic rhythm of the poet shows us the internal rhythm and internal rhyme clearly in various sections of the poems as an expression of the poetic condition and morality of the poems.